PERLINDUNGAN HUKUM TUNJANGAN HARI RAYA PEKERJA YANG TIDAK DI BERIKAN OLEH PT GUNBUSTER NICKEL INDUSTRI (GNI) SULAWESI TENGAH - pakaya, asriani; Nur Insani; Aliyas, Aliyas (Fakultas Hukum Universitas Ichsan Gorontalo, 2024)
ASRIANI. H1120013. LEGAL PROTECTION OF WORKERS' HOLIDAY ALLOWANCES IGNORED BY PT.GUNBUSTER NICKEL INDUSTRI (GNI) CENTRAL SULAWESI This research aims to find out: (1) the legal efforts of workers' unpaid holiday allowances by PT Gunbuster Nickel Industry (GNI) Central Sulawesi, and (2) the legal protection of workers' unpaid holiday allowances by PT Gunbuster Nickel Industry (GNI) Central Sulawesi. This research employs an empirical juridical legal research method. Empirical juridical research is legal research on the enactment or implementation of normative legal provisions on any specific legal events that occur in society. The research results indicate that: (1) The legal efforts of workers' unpaid holiday allowances by PT Gunbuster Nickel Industry (GNI) Central Sulawesi are carried out based on mutual agreement betweenworkers and companies without coercion so that there is no religious holiday allowance for workers, (2) To find out thelegal protection of workers' unpaid holiday allowances by PT Gunbuster Nickel Industry (GNI) Central Sulawesi protection provided by the company to workers in the form of safety at work and the company's concern for its workers. The protection of workers is regulated in Law No. 13 of 2003 and the Regulation of the Minister of Labor providessanctions against companies that do not provide holiday allowances to workers in the form of written warnings, restrictions on business activities, temporary suspension of production equipment partially or completely, and suspension of business activities. (1) Obstacles come from the workers themselves because of the low level of education and the feeling of fear so that workers do not question or set aside the rights they should get. (2) Sanctions should be stricter than administrative sanctions. Additional sanctions such as imprisonment are expected to reduce the level of violation of religious holiday rights. Keywords: worker protection, THR, Regulation of the Minister of Labor No.6 of 2016